2011
DOI: 10.1039/c1ob05146f
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on the inactivation mechanism of γ-aminobutyric acid aminotransferase

Abstract: The inactivation mechanism of γ-aminobutyric acid aminotransferase (GABA-AT) in the presence of γ-vinyl-aminobutyric acid, an anti-epilepsy drug, has been studied by means of theoretical calculations. Density functional theory methods have been applied to compare the three experimentally proposed inactivation mechanisms (Silverman et al., J. Biol. Chem., 2004, 279, 363). All the calculations were performed at the B3LYP/6-31+G(d,p) level of theory. Single point solvent calculations were carried out in water, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 44 publications
5
21
0
Order By: Relevance
“…The use of solvent molecules in the assistance of the proton transfer steps, as in the case here, has proven to be crucial because the solvent serves as the proton conduit 30. Furthermore, several studies have shown that reactions involving the carbonyl functionality, such as peptidic amides, first interconvert into their more reactive tautomeric counterparts; these tautomerization steps were also shown to be facilitated by polar protic solvents 30d,f,g,i…”
Section: Resultsmentioning
confidence: 99%
“…The use of solvent molecules in the assistance of the proton transfer steps, as in the case here, has proven to be crucial because the solvent serves as the proton conduit 30. Furthermore, several studies have shown that reactions involving the carbonyl functionality, such as peptidic amides, first interconvert into their more reactive tautomeric counterparts; these tautomerization steps were also shown to be facilitated by polar protic solvents 30d,f,g,i…”
Section: Resultsmentioning
confidence: 99%
“…All of the syntheses were carried out under an atmosphere of argon using flame-dried glassware. 1 H NMR and 13 C NMR spectra were recorded on a Bruker AVANCE III 500 spectrometer at 26 °C using DMSO-d 6 or CDCl 3 as solvents. Chemical shifts are reported in parts per million (ppm, δ) and referenced to DMSO-d 6 (2.50 ppm for 1 H NMR and 39.52 ppm for 13 C NMR) or CDCl 3 (7.26 ppm for 1 H NMR and 77.2 ppm for 13 C NMR).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…1 H NMR and 13 C NMR spectra were recorded on a Bruker AVANCE III 500 spectrometer at 26 °C using DMSO-d 6 or CDCl 3 as solvents. Chemical shifts are reported in parts per million (ppm, δ) and referenced to DMSO-d 6 (2.50 ppm for 1 H NMR and 39.52 ppm for 13 C NMR) or CDCl 3 (7.26 ppm for 1 H NMR and 77.2 ppm for 13 C NMR). Coupling constants (J) are reported in Hz, and spin multiplicities are described as s (singlet), br (broad singlet), d (doublet), t (triplet), q (quartet), and m (multiplet).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Density functional theory at the B3LYP/6-31+G(d,p) level of theory was used to differentiate the energies of the three inactivation mechanisms (Scheme 12, pathway a; Scheme 12, pathway b; and Scheme 14). 99 The conclusion that the mechanism in Scheme 14 is least likely, the enamine mechanism (Scheme 12, pathway b) is next likely, and the Michael addition mechanism (Scheme 12, pathway a) is the most energetically favorable, are consistent with the experimental findings. Their calculations of the geometry of Michael adduct 65 also agree well with the X-ray structure.…”
Section: Chemical Reviewsmentioning
confidence: 99%